Quinalphos induced histopathological changes in the gill, liver and kidney of the freshwater fish, Labeo rohita - M.S JUGINU,; T. SUJILA, (International Journal of Pharma and Bio Sciences, 2019)
Quinalphos is one of the most widely used organophosphate pesticides in agriculture. In agriculture, a large number of pesticides are used to control agricultural pests but it adversely affects many non-targeted species like fish. As the fish is a good indicator of aquatic pollution, the histopathological studies in its internal organs are more valuable which gives important information about the health status of the animal as well as the current status of the habitat in which the fish lives. The focus of the study is to determine the histopathological damage of Gill, Liver and Kidney in freshwater fish, Labeo rohita after sublethal exposure (6.06 ppm) to Quinalphos. The organs of the exposed individuals showed remarkable changes such as degeneration of epithelial lining, epithelial proliferation in gills, clumping of nucleus, degenerated hepatocyte cells, fatty degeneration in liver and in kidney shrinkage of the glomerulus and dilation of tubular lumen in comparison with control which was maintained in parallel. The results of the current research denoted that the gills of freshwater fish are the first target organ of several xenobiotics because of their direct contact with the water. Similarly, the liver and kidney are generally regarded as the central organs of xenobiotic metabolism in fish and alterations in its structure may be useful as biomarkers that indicate prior exposure to environmental stressors.